Experimental study on a novel hybrid system of active composite PCM wall and solar thermal system for clean heating supply in winter. (1st January 2020) - Kong, Xiangfei; Wang, Lu; Li, Han; Yuan, Guangpu; Yao, Chengqiang
Highlights: A novel phase change material (PCM) wallboard with grooves has been fabricated. Solar thermal system was coupled with PCM wallboard through capillaries. The hybrid system has reduced the indoor temperature fluctuation. PCM wallboard extended the service time of solar thermal system. The coupling use of PCM and solar energy enhanced building energy efficiency. Abstract: Building is a significant contributor to high energy consumption and its associated environmental effects. Hence, there had been a continuous drive towards alternative active and passive options for creating a thermally comfortable environment at lower energy penalty. The incorporation of phase change material (PCM) with building envelope appears as one of passive techniques for building energy efficiency. Solar thermal energy, a renewable energy, has an unsteady problem that restricts its application on the space heating. Therefore, PCM wallboard (passive option) coupling with solar thermal system (active option) to form a hybrid system can enhance the thermal performance of building envelope and meanwhile maintain a comfortable indoor thermal environment with a sustainable and cleaning energy supply under the winter condition. In this study, a novel expanded perlite-based composite phase change material wallboard has been fabricated and then combined with solar thermal system by capillaries. Strategy experiments were comparatively conducted in two real scale experimental rooms (PCM room and reference room). PCM wallboards coupling with solar thermal system have been installed on the internal surface of PCM room, and the reference room is the same as PCM room, except that there is no PCM wallboard. The results showed that PCM wallboards with excellent mechanical ability and thermal property performed well in their integration with solar thermal system, and this hybrid system has reduced daily energy consumption by 44.16%. Therefore, it can be concluded that the novel hybrid system composed of PCM wallboard and solar thermal system has a significant application potential on maintaining a comfortable indoor environment and enhancing building energy efficiency.